The Production of Independent Popular Music during the COVID-19 Pandemic in Guayaquil City - Perez-Valero, Luis (Global Journal of Cultural Studies, 2023)
This work delves into the profound impact of the COVID-19 pandemic on Guayaquil's music scene, with a focus on the adaptation strategies of independent music producers. Drawing on the concepts of musical scenes proposed by Bennet and Peterson (2004), the study reveals how a traditional local music scene shifted towards a virtual one, impacting various cultural circuits. The pandemic necessitated the migration of music production and recording processes to digital platforms, revolutionizing the modes of listening and audio production. The study employs a qualitative, descriptive, and exploratory research approach, encompassing field research, netnography, and ethnomusicology. It offers a holistic understanding of how independent producers coped with the challenges of the pandemic and continued their work.